Patterning of interactive metadiscourse markers in result and discussion sections of academic research articles across disciplines - Khedri, Mohsen; Ebrahimi, Seyed Jamal; Chan, Swee Heng (Universiti Putra Malaysia Press, 2013)
A generic analysis of research articles can cover a wide variety of issues; among them are rhetorical features. A crucial part of the rhetorical features of research article is the use of metadiscourse that can help to make the text persuasive and acceptable to a discourse community (Hyland, 2005). The underlying principle behind metadiscourse use is the view of writing as socially engaging: in particular metadiscourse reveals the ways writers project themselves into their discourse to declare their perspectives and commitments to the readers. The present paper focuses on interactive metadiscourse markers in the result and discussion sections of academic research articles across four disciplines, namely, English Language Teaching, Civil Engineering, Biology, and Economics to clarify the manner of metadiscourse use among the varied disciplines. Sixteen research article result and discussion sections (4 from each discipline) were sourced from four internationally reputed refereed journals for analysis. Results indicated some cross-disciplinary similarities and differences in the use of interactive metadiscourse markers. Results of this study can be of value especially for novice research article writers who belonged to disciplinary communities focused in the present study so that they get an entry into their own particular research communities.